Fit für den Klimawandel: Wie passt sich Wien an? - Steiner, Marianne (My University, 2017)
Geschildert werden Handlungsfelder und Maßnahmen des Wiener Klimaschutzprogramms (KliP Wien) und des Urban Heat Island-Strategieplans (UHI STRAT).

For the past 16 years, Vienna has had a broad climate protection programme known as KliP Vienna. The current program is valid until 2020 and includes 385 individual measures in the fields of energy production and use of energy, mobility and city structure, procurement, waste management, agriculture and forestry, nature conservation and public relations. In addition KliP contains some considerations about Viennese climate adaption measures to elaborate more concretely in coming years. Therefore 2011 the City of Vienna was starting a concrete adaption strategy based on KliP managed by the Executive Office for the Co-ordination of Climate Protection Measures. There are a lot of adaption-measures which have been implemented independently. Especially concerning flood control Vienna has a long tradition, for instance on the Danube. Important steps were also done to improve fresh water supply and buildings. Now we have to define what additional measures are necessary. These tasks will be done within the scope of working groups. They have to collect the existing adapting measures in Vienna and work out proposals for suitable measures. Then the measures will be submitted to stakeholders and politicians for decision. The main topics are health, energy and water supply, urban planning, traffic, city vegetation, agriculture and forestry. An important measure of the City of Vienna relating to urban planning is the construction and promotion of green roofs and green facades. This measure includes amongst others a special support programme since many years. Vienna takes part in "Urban Heat Islands" (UHI), which is an EU-wide project. An UHI is a microclimatic phenomenon in the metropolitan or city areas. In these areas there are significantly higher temperatures than in the surrounding peri-urban and rural areas. The Viennese UHI-Strategy-Plan includes several measures how to cool down urban heat islands and offers indicators about the efficiency of these measures. In the health sector, a heat guide for the Viennese population was published. A heat action plan is in process. Within the scope of energy supply and consumption an Energy Security Plan and a Renewable Action Plan has been developed but have still to be agreed upon by the Viennese city council. Due to the increasing summer temperatures in Vienna a special focus has been placed on the promotion of passive cooling.
Keywords: Großstadt; Klimawandel; Klimaeinfluss; Stadtklima; Aufheizung; Hitze; Wärmeinsel; Kommunaler Klimaschutz; Klimaschutzprogramm; Klimaanpassung; Hitzeschutz; Kühlung